2005
DOI: 10.1111/j.1398-9995.2006.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

Cysteinyl‐leukotrienes contribute to sputum eosinophil chemotactic activity in asthmatics

Abstract: Background: Cysteinyl-leukotrienes are lipid derived mediators involved in asthma. They are able to stimulate eosinophil chemotaxis in vitro. Induced sputum from asthmatics has been shown to contain eosinophil chemotactic activity. The purpose of our study was to evaluate the contribution of cysteinyl-leukotrienes to sputum eosinophil chemotactic activity in asthmatics and to seek whether there might be differences between asthmatics free of inhaled corticosteroids vs those regularly receiving this treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Previous investigations have established that eotaxins induce maximal transendothelial eosinophil migration, with respect to the other chemokines in the following order of strength: eotaxin-2>RANTES>MCP-4>IL-5>LTB4 [16][17][18][19]. Many chemokines act by binding to the several receptors, whereas all eotaxins operate by stimulation of the same receptor, CCR3 [20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have established that eotaxins induce maximal transendothelial eosinophil migration, with respect to the other chemokines in the following order of strength: eotaxin-2>RANTES>MCP-4>IL-5>LTB4 [16][17][18][19]. Many chemokines act by binding to the several receptors, whereas all eotaxins operate by stimulation of the same receptor, CCR3 [20].…”
Section: Discussionmentioning
confidence: 99%
“…In the tissues at sites of allergic inflammation, a variety of inflammatory cells, including eosinophils, likely generate cysLTs, therefore the eosinophils in such tissues may be exposed to higher concentrations of cysLTs than those measured in the sputum samples. In this context, Hemelaers et al [24] recently reported that eosinophil chemotactic activity in the sputum from both corticosteroid-naive and corticosteroid-treated asthmatic patients was inhibited by montelukast, suggesting that cysLT actively participated in the eosinophil chemotactic activity in the asthmatic airway.…”
Section: Discussionmentioning
confidence: 99%
“…No association was observed between Cyst-LTs and eosinophils in non-smoking asthmatics. This might be due to the lower levels of CystLTs, as there is evidence that Cyst-LTs contribute actively in sputum eosinophilic activity in asthma [26].…”
Section: Discussionmentioning
confidence: 99%